PENGARUH REWARD DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA HONDA BINTANG MOTOR KOTA BENGKULU - Mince Hermayani; Islamuddin Islamuddin (UM. Bengkulu, 2022)
This study aims to determine the effect of Reward (X1) and Work Discipline (X2) on Employee Performance (Y) at Honda Bintang Motor Bengkulu City, either partially or simultaneously. The objects in this study were the employees of Honda Bintang Motor in Bengkulu City, amounting to 56 people. In this study the authors used quantitative methods and data collection by means of observation, interviews and questionnaires. The data analysis technique used instrument test, classical assumption test, analysis of respondents' responses, multiple linear regression analysis, determinant coefficient (R2), and also hypothesis testing. Based on the results of multiple linear regression analysis, the equation Y = 11.324 + 0.326X1 + 0.257 (X2) +e. This equation can be explained by the positive influence of each independent variable, namely Reward (X1) and Work Discipline (X2) on employee performance (Y). The value of the coefficient of determination (R2) from R Square is 0.609, this result shows that the variable Reward (X1) and Work Discipline (X2) affect employee performance (Y) by 60.9% while the remaining 39.1% is influenced by other variables that not investigated in this study. Based on the results of hypothesis testing with the t test showing the Reward variable (X1), the tsign value < 0.000, it can be concluded that the reward has a significant influence on employee performance (Y), the Work Discipline variable (X2) obtained the tsign value < 0.003, it can be concluded that the discipline work has a significant influence on employee performance (Y). Based on the results of hypothesis testing using the F test, the Fsign value is 0.000b < 0.05. This means that together Reward (X1) and Work Discipline (X2) have a significant effect on Employee Performance (Y) at Honda Bintang Motor Bengkulu City. Keywords : Reward, Work Discipline, Employee Performance